Managing Infographic-Mediated Indonesian Language Instruction to Improve Elementary Students' Procedural Writing Skills - Sisca Rachmawati; Nana Herdiana Abdurrahman (Journal of Innovation and Research in Primary Education, 2026)
Elementary students frequently encounter challenges in developing writing proficiency due to inadequate instructional strategies and limited engagement with conventional text-based approaches. This study examined the management of Indonesian language instruction incorporating infographic media to enhance elementary students' procedural writing skills through systematic PDCA (Plan-Do-Check-Act) cycle implementation. A qualitative multiple case study was conducted at two elementary schools (SDN Sindanglaya and SDN Panagan) in Cianjur Regency, Indonesia. Data were collected through classroom observations (24 sessions), semi-structured interviews with teachers (n=4), principals (n=2), and students (n=48), and document analysis of instructional artifacts. Data analysis followed Miles et al.'s systematic procedures encompassing data reduction, display, and conclusion drawing with cross-case comparison. Findings revealed that structured infographic-based instructional management significantly improved students' writing quality (34% average improvement) with particularly substantial gains in structural organization (47%). Student engagement during infographic activities (78%) substantially exceeded traditional instruction (52%). Teachers demonstrated pedagogical adaptability despite technological constraints, while systematic evaluation and continuous improvement processes enhanced instructional effectiveness.  PDCA-based management of infographic-mediated instruction represents an effective, evidence-based approach for enhancing elementary writing instruction when implemented through comprehensive frameworks encompassing rigorous planning, adaptive pedagogy, systematic evaluation, and continuous refinement that balance innovation with pragmatic implementation realities.